2014
DOI: 10.1002/rcm.6896
|View full text |Cite
|
Sign up to set email alerts
|

Laser desorption ionization time‐of‐flight mass spectrometry of erbium‐doped Ga‐Ge‐Sb‐S glasses

Abstract: The local structure of Ga-Ge-Sb-S glasses is at least partly different from the structure of species identified in plasma by mass spectrometry, as deduced from Raman scattering spectroscopy analysis; these glasses are mainly formed by [GeS4/2]/[GaS4/2] tetrahedra and [SbS3/2] pyramids. Extended X-ray absorption fine structure measurements show that Er(3+) ions in Ga-Ge-Sb-S glasses are surrounded by 7 sulphur atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
(103 reference statements)
1
18
0
Order By: Relevance
“…The peak position exhibited an obvious red-shift in the 1 mol% Er 3+ -doped glass sample, which coincide with the ratio exceeding the critical point. As reported by Petr Nemec through mass spectra measurement, this phenomenon was attributed to the fact that the two erbium-containing species contain gallium atoms (GaSb 2 SEr + and GaS 6 Er 2+ )36. The second cluster corresponds to the structural fragment (suggested in the literature for high concentration of erbium and gallium), which could be involved in the clustering effect of the higher addition of Ga and Er samples.…”
Section: Resultsmentioning
confidence: 57%
“…The peak position exhibited an obvious red-shift in the 1 mol% Er 3+ -doped glass sample, which coincide with the ratio exceeding the critical point. As reported by Petr Nemec through mass spectra measurement, this phenomenon was attributed to the fact that the two erbium-containing species contain gallium atoms (GaSb 2 SEr + and GaS 6 Er 2+ )36. The second cluster corresponds to the structural fragment (suggested in the literature for high concentration of erbium and gallium), which could be involved in the clustering effect of the higher addition of Ga and Er samples.…”
Section: Resultsmentioning
confidence: 57%
“…In case of GeSe 4/2 tetrahedron, forming one of the most important structural feature as proved by Raman data of the glasses/films, LDI TOFMS detected probably fragments of such structural entities, namely GeSe c + ( c = 1–2) clusters. It is worthy to note that all the mass spectra show lower number of Ge‐based clusters than one could expect with respect to the stoichiometry of studied glasses; this fact could probably be explained by difficult ionization of germanium and germanium‐based clusters …”
Section: Resultsmentioning
confidence: 88%
“…It has been already shown that Laser Desorption Ionization Time‐of‐Flight Mass Spectrometry (LDI TOFMS) is a powerful and useful technique to generate and study clusters of various solid materials including chalcogenide glasses; it was demonstrated that this technique can help to determine structural fragments of As–Se and Ga–Ge–Sb–S materials in solid as well as in plasma state . The phase change memory Ge 2 Sb 2 Te 5 bulk materials, their thin films, and Ge–As–Te materials were also analysed by LDI TOFMS …”
Section: Introductionmentioning
confidence: 99%
“…For mid-IR emissions, chalcogenide glasses proved their efficiency by reducing the multiphonon relaxation of emitting levels and the ∼340 cm −1 phonon energy of the sulfide glass is enough high to provide an efficient population of the 6 H 11/2 manifold when optically pumped into higher-lying manifolds (Tables 1 and 2). To be precise about phonons energy of bulk Ga 5 Ge 20 Sb 10 S 65 glass, the Raman scattering spectrum corresponds to a broad band between 260 and 450 cm −1 , which is composed of several overlapping bands peaking at 295, 340, 370 and 430 cm −1 [15,22]. Three main bands, with decreasing intensity from 340, 370 to 430 cm −1 , have been typically reported related to [GeS 4 ] tetrahedra vibration modes.…”
Section: Resultsmentioning
confidence: 98%